Dewey on Education / Selections with an Introduction and Notes by Martin S. Dworkin - Dworkin Martin S (Teachers College Press, 1959)
The classics in Education series presents the sources of our educational heritage. John Dewey: A Centennial Review, My Pedagogy Creed, The School and Society, The School and Social Progress, The School and the Life of the Child, Waste in Education, The Child and the Curriculum, Progressive Education and the Science of Education, Introduction by John Dewey to the Use of Resources in Education by Elsie Ripley Clapp.